MAPPING ESTIMATION OF SHALLOW WATER DEPTH USING BATHYMETRIC EMPIRICAL MODELING ECHOSOUNDER DATA AND SENTINEL-2 SATELLITE IMAGE DATA (CASE STUDY: SHALLOW WATERS OF BAYUR BAY, PADANG CITY) - Altha Nurzafira Melin; Dian Adhetya Arief (International Remote Sensing Applied Journal, 2021)
This study aims to see the depth of the shallow waters of Teluk Bayur, Padang City, West Sumatra Province using Sentinel 2 imagery through the processing of Geographic Information Systems and Remote Sensing. Satellite imagery is intended to obtain in-depth information at an affordable cost and to examine differences in the use of the algorithms used. This study uses Sentinel 2 satellite data. The algorithm used in this research is Bathymetric Empirical Modeling which is applied to Sentinel-2 digital satellite imagery, it will go through several analytical processes, starting from the extraction of water bodies where this process separates between water bodies and non-water bodies. waters, after that the process of correcting the reflection of the water surface or Sunglint. The results of this study are empirical maps of the shallow waters of Teluk Bayur which get a maximum depth of 125 m using band 1 and band 2, while the maximum depth that is more accurate is 128 m using band 2 and band 3 where the maximum depth of 128 m is also the depth of data acquisition results echosounder PT. PELINDO II Teluk Bayur Branch.